Risk factors for malnutrition in under-five children: one year after the Yogyakarta earthquake - Neti Nurani; Mei Neni Sitaresmi; Djauhar Ismail (Paediatrica Indonesiana, 2011)
Background Malnutrition in children under the age of five remains a major health problem, since half of mortality cases in this age group involve malnutrition. The 2006 earthquake caused destruction of physical, biological and socio-economic environments, potentially leading to malnutrition in Yogyakarta children.Objective To identify the prevalence and risk factors of malnutrition in Yogyakarta children under five years of age, one year after the 2006 earthquake.Methods We conducted a cross-sectional study among children aged 0 to 60 months in the Bambanglipuro Subdistrict, Bantul Regency, Yogyakarta from September to October 2007. Nutritional status was determined using weight for height Z-scores, according to the WHO 2006 Child Growth Standards.Results Out of 666 subjects, we found severe malnutrition, undernutrition, normal weight, and overweight status in 1.7%, 4.8%, 88.6% and 4.8%, respectively. By multivariate analysis, risk factors for malnutrition were not having been weighed during the previous three months (OR 0.35; 95% CI 0.1 to 0.8) and having acute respiratory infection in the previous two weeks (OR 1.99; 95% CI 1.1 to 3.8)Conclusion One year following the 2006 earthquake, acute respiratory infection in the previous two weeks and unmonitored growth in the previous three months were risk factors for malnutrition in children under five years.